2022
DOI: 10.1002/jcla.24257
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine pathway in Coronavirus disease (COVID‐19): Potential role in prognosis

Abstract: Background It is known that inflammatory responses play an important role in the pathophysiology of COVID‐19. Aims In this study, we aimed to examine the role of kynurenine (KYN) metabolism on the severity of COVID‐19 disease AQ5. Materials & Methods Seventy COVID‐19 patients of varying severity and 30 controls were included in the study. In addition to the classical laboratory parameters, KYN, tryptophan (TRP), kynurenic acid (KYNA), 3 hydroxykynurenine (3OHKYN), quinolinic acid (QA), and picolinic acid (PA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
(90 reference statements)
4
23
0
1
Order By: Relevance
“…We found increases in several kynurenine pathway metabolites, such as KYN, QUIN, 3-HK and PIC, together with higher levels of IL-6. Additionally, the increased levels in QUIN/TRP, QUIN/KYN, QUIN/KYNA and KYN/TRP, further support a recent published study by Cihan and colleagues (23). Pro-inflammatory pathway proteins, along with metabolites from the kynurenine pathway were significantly increased in patients that presented with both COVID-19 and hypertension when compared to COVID-19 patients that were not hypertensive.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We found increases in several kynurenine pathway metabolites, such as KYN, QUIN, 3-HK and PIC, together with higher levels of IL-6. Additionally, the increased levels in QUIN/TRP, QUIN/KYN, QUIN/KYNA and KYN/TRP, further support a recent published study by Cihan and colleagues (23). Pro-inflammatory pathway proteins, along with metabolites from the kynurenine pathway were significantly increased in patients that presented with both COVID-19 and hypertension when compared to COVID-19 patients that were not hypertensive.…”
Section: Discussionsupporting
confidence: 88%
“…We found increases in several kynurenine pathway metabolites, such as KYN, QUIN, 3-HK and PIC, together with higher levels of IL-6. Additionally, the increased levels in QUIN/TRP, QUIN/KYN, QUIN/KYNA and KYN/TRP, further support a recent published study by Cihan and colleagues (23).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The L-kynurenine/L-tryptophan ratio has been extensively studied in inflammatory diseases since was introduced decades ago as an index of tryptophan breakdown ( 54 ). In the context of COVID-19 infection, this ratio has also been explored ( 9 , 13 , 15 ) as it is related to the inflammatory state in COVID-19, and can be used in treatment decision ( 55 ), with some studies describing an increase in the L-kynurenine/L-tryptophan ratio associated with COVID-19 severity ( 55 , 56 ), poor prognosis ( 57 , 58 ),) and mortality ( 58 60 ),,. Consistently with these studies, we observed an upregulation of L-kynurenine and downregulation of L-tryptophan in severe COVID-19 patients, indicating an elevated L-kynurenine/L-tryptophan ratio, which suggests a disease-associated hyperactivation of the indoleamine-pyrrole 2,3-dioxygenase (IDO) enzyme.…”
Section: Discussionmentioning
confidence: 99%